Reclaiming Old World Bluestem Pasture with Imazapyr Application and Native Grass Overseeding - Keith Harmoney (Kansas Agricultural Experiment Station Research Reports, 2022)
Old world bluestems (OWB), mainly Caucasian bluestem (Bothriochloa bladhii) and yellow bluestem(Bothriochloa ischaemum)introduced from parts of eastern Europe, Asia, Africa, and Australia, have been shown to reduce abundance and diversity of some insect and wildlife species compared to native grasses when these OWB grasses form dense stands. These OWBs have been invading native pastures in the southern Great Plains and are rapidly increasing in the amount of area occupied in Kansas. Two landowners purchased pasture property in Ellsworth County, KS, and observed that Caucasian old world bluestem had increased in the pasture significantly over the course of several years. They developed a plan with local partners to reclaim the pasture back to native grass and forb dominance in an effort to improve wildlife habitat and cattle grazing on the property.
Keywords: broadcast spray; dicamba; no-till drill; plant frequency; prescribed burn; seed bank; vegetative cover; old world bluestem; imazapyr